Prevenção à saúde: conceitos, determinantes e efeito na aposentadoria precoce - Carvalho, Fabrícia Jóisse Vitorino (2021)
This thesis consists of three chapters. The first one brings a theoretical approach, and deals with the levels of primary, secondary and tertiary prevention. The second and third chapters are empirical constructions, and use the 2019 National Health Survey (PNS) database. The first chapter shows that primary prevention consists of a set of actions that reduce risk factors and increase the well-being and health of the individual; secondary prevention can be defined as early diagnosis and treatment of diseases; and tertiary prevention occurs when the individual already has the comorbidity and tries to reduce complications and disease progression. In the second chapter, an investigation was carried out on health prevention for men and women; regarding the levels of primary, secondary and tertiary prevention. The main results of this chapter show that access is a determining factor for the realization of preventive attitudes to health in its different developments. In primary prevention, for example, having access to places that favor physical activity practices increases the individual’s predisposition to adopt good health habits, while living with a smoker in the same household reduces the individual’s predisposition to adopt primary preventive attitudes the health. Identifying the factors that drive the adoption of preventive attitudes (primary, secondary and tertiary) is important to obtain a higher level of health and well-being for the individual; to reduce costs for the SUS with hospital admissions and services; and for the entire economy, from the increase in productivity, the reduction of disability benefits, and the containment of premature deaths resulting from preventable pathologies. Finally, the third chapter investigates the effect of health prevention levels on Brazilians’ early retirement. The assumed hypothesis was that carrying out prevention reduces the number of early retirees in Brazil. The main results of this last chapter show that the higher the level of primary and tertiary prevention, the lower the probability of Brazilians retiring early. The evidence found confirms the hypothesis assumed at the beginning of this work, and highlights the economic importance of encouraging individuals to carry out health prevention when it is desired to obtain a reduction in the social security burden and productivity gains, with the permanence of individuals of working age in the market of work.